1988
DOI: 10.1002/cjce.5450660515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzene and thiophene on rate of coke formation during naphtha pyrolysis

Abstract: The effect of benzene or thiophene addition to the feed on the rates of coke formation during naphtha pyrolysis has been investigated in a jet‐stirred reactor at atmospheric pressure in the temperature range of 1073‐1103 K. In addition, the effect of temperature, space time, weight ratio of steam to naphtha and the material of construction on the rate of coke deposition was also studied. The rate of coke formation increased as the temperature, space time and aromatic content of the feed was increased whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…As can be seen from this figure, the asymptotic coking rate on coated Inconel plate was reduced by approximately 67 % . For uncoated plates, the rate of coke deposition was initially high and then decreased to a constant value after approximately 2 hours, in agreement with the results reported by other workers (Newsome and Leftin, 1979;Kumar and Kunzru, 1985;Sahu and Kunzru, 1988). The decrease of coking rate with run time on coated metal surfaces has been explained on the basis of the continuous decrease of the catalytic activity of the metal wall due to coke coverage.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As can be seen from this figure, the asymptotic coking rate on coated Inconel plate was reduced by approximately 67 % . For uncoated plates, the rate of coke deposition was initially high and then decreased to a constant value after approximately 2 hours, in agreement with the results reported by other workers (Newsome and Leftin, 1979;Kumar and Kunzru, 1985;Sahu and Kunzru, 1988). The decrease of coking rate with run time on coated metal surfaces has been explained on the basis of the continuous decrease of the catalytic activity of the metal wall due to coke coverage.…”
Section: Resultssupporting
confidence: 90%
“…The catalytic effect of the reactor walls on coke formation is well documented (e.g., Albright et al, 1979;Sahu and Kunzru, 1988;Baker, 1990) and most of the methods used to inhibit coking employ some means to passivate the reactor walls. A technique commonly used to reduce coke formation is to either presulfide the reactor (Crynes and Albright, 1969;Trimm and Turner, 1981;Shah et al, 1976) or to add sulfur compounds to the feed (Bajus et al, 1981;Sahu and Kunzru, 1988). Baker and Chludzinski (1980) studied the effect of various oxide additives on the growth of filamentous carbon on iron-nickel surfaces.…”
mentioning
confidence: 99%
“…These results are consistent with the work of Sahu and Kunzru, who studied the influence of thiophene on naphtha pyrolysis. [5] The authors noticed an increased rate of pyrolysis and a lower yield of aromatics. [5] The increased rate of pyrolysis was explained by radical transfer from the sulfur compounds, which decompose faster, to the hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The authors noticed an increased rate of pyrolysis and a lower yield of aromatics. [5] The increased rate of pyrolysis was explained by radical transfer from the sulfur compounds, which decompose faster, to the hydrocarbons. The reactions responsible for this radical transfer are hydrogen abstraction reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In a review reported by Baker on the catalytic mechanism for the growth of carbon filaments, it was concluded that the available theories on this phenomenon failed to account for all the aspects of the experimental results [4]. Also, numerous experimental assessments, directed to the coke formation kinetics, have been published [5][6][7].…”
Section: Introductionmentioning
confidence: 94%